Studi Kelayakan Bisnis Studi Kasus Di Umkm Jagung Goreng Sukma, Payakumbuh - Marlina, Winny Alna (Jurnal Manajemen, 2021)
Sukma Fried Corn Business is one of fried corn MSME business that is developing in Payakumbuh. This business has problems in the marketing, technical, and environmental aspects. Feasible study or business feasibility study is very useful for MSME owners, because it helps them in terms of product design and variety, waste management, production optimization by modifying the layout, management and organizational aspects which are common problems for MSMEs. The target of this research is to make standard product variants and packaging and modified layout. The Research Method is Qualitative descriptive. The data collection technique used in this study was the direct observation of MSMEs and focused on observing : Production System, Layout, Machines and equipment used and Waste generated. Results: In terms of market and marketing aspects, Sukma Fried Corn is innovating in adding flavor variants for its products. It is conducting promotions with both electronic and printed medias, to expand the reach of the target markert. In addition, it also created a unique and attractive product packaging design so that consumers can easily recognize their products. Concerning the layout of the facility, Sukma fried corn is working on separating the frying room and the packing room